LEGAL PROTECTION FOR MEDICAL PERSONNEL IN INDONESIA: ANALYSIS OF THE 2023 HEALTH LAW AND ITS IMPLEMENTATION IN PROTECTING HEALTH WORKERS PRACTISING IN ACCORDANCE WITH PROFESSIONAL STANDARDS - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Legal protection for medical personnel is a crucial issue in the Indonesian health system, especially since medical personnel are often vulnerable to lawsuits even though they have practised in accordance with professional standards. This study aims to analyse the forms of legal protection for medical personnel as stipulated in Law No. 17 of 2023 on Health and to examine its implementation in health service practice. The research method used is normative juridical with a legislative and conceptual approach, supported by relevant primary and secondary legal materials. The results show that the 2023 Health Law has normatively strengthened protection for medical personnel by emphasising that any medical personnel who act in accordance with professional standards, service standards, and professional codes of ethics cannot be automatically prosecuted. However, the implementation of legal protection in the field still faces serious challenges, including limited derivative regulations, low legal literacy among medical personnel, inconsistent understanding among law enforcement officials, and a lack of advocacy from professional organisations. These conditions result in the legal protection promised by the law often not being felt in practice by medical personnel in the field. Thus, this study concludes that legal protection for medical personnel is strong in terms of norms but weak in terms of implementation. To ensure its effectiveness, concrete steps are needed in the form of drafting more operational derivative regulations, increasing the legal literacy of medical personnel, strengthening the role of professional organisations, and training law enforcement officials on health law. These efforts are expected to create a more fair, balanced, and effective legal protection mechanism, enabling medical personnel to perform their professional duties safely and ensuring the public continues to receive quality healthcare services.